1992
DOI: 10.1007/bf01981503
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-related nephrotoxicity due to 1,2-dichloropropane in vitro

Abstract: Sex- and age-related nephrotoxicity due to 1,2-dichloropropane was studied in vitro by means of renal cortical slices obtained from Wistar rats. Reduced glutathione content, organic anion accumulation (p-aminohippurate), and release of malondialdehyde (to measure the extent of lipid peroxidation), aspartate aminotransferase, gamma-glutamyltransferase and lactate dehydrogenase into the incubation medium were determined. Sex differences in naive rats parameters were slight, but male were more susceptible to toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…1,2-Dichloropropane causes nephrotoxic effects via mercapturic acid metabolism [109]. In vitro, renal cortical slices prepared from male Wistar rat kidney were more sensitive to DCP effects than those from females [110]. Further, in a classic sex hormone paradigm study, Odinecs et al [111] confirmed that male rats are more sensitive than females and that testosterone plays a pivotal role in nephrotoxicity.…”
Section: 2-dibromoethane and 12-dibromo-3-chloropropanementioning
confidence: 97%
“…1,2-Dichloropropane causes nephrotoxic effects via mercapturic acid metabolism [109]. In vitro, renal cortical slices prepared from male Wistar rat kidney were more sensitive to DCP effects than those from females [110]. Further, in a classic sex hormone paradigm study, Odinecs et al [111] confirmed that male rats are more sensitive than females and that testosterone plays a pivotal role in nephrotoxicity.…”
Section: 2-dibromoethane and 12-dibromo-3-chloropropanementioning
confidence: 97%